Reaction of Imidoformates with Anthranilates: Facile, One‐Pot, Three‐Component Synthesis of 8H‐Quinazolino[4, 3‐b]quinazolin‐8‐ones 1. (5th August 2013) - Venkateswarlu, S.; Satyanarayana, M.; Ravikiran, P.; Siddaiah, V.
Abstract : Abstract : We report a facile, one‐pot, three‐component methodology for the synthesis of 8 H ‐quinazolino[4, 3‐b]quinazolin‐8‐ones from commercially available 2‐aminobenzonitriles, triethyl orthoformate, and anthranilic acids/esters/amides in good yields.